Syntax and morphology in Williams syndrome - Clahsen, Harald; Almazan, Mayella (Cognition, 1998)
Williams syndrome (WS) is a neuro-developmental disorder which is characterized by an unusual fractionation of language abilities and other cognitive functions. We have investigated four cases of English-speaking subjects with WS, and we show that despite their low IQs the WS children's performance on syntactic tasks and on regular inflection is not impaired. Irregular inflection, however, is affected causing many errors. We also report results from studies investigating the same linguistic phenomena in children with specific language impairment. These children exhibit a different pattern of impairment, with relatively poor performance on syntactic tasks and regular inflection. We suggest a linguistic characterization of the morphosyntax in WS according to which WS subjects are impaired in accessing (particular kinds of) information from lexical entries, with their computational system for language appearing to be intact. We interpret the selective impairments found in WS and SLI as supporting the theoretical distinction between a computational system and an associative memory system for language.